Enhancement of lung cancer nodules in chest x-ray using morphological transformation function / Rafidah Supar ... [et al.] - Supar, Rafidah; Sazali, Nur Hanis Hazwani; Sharip, Hairenanorashikin; Md Yamin, Lyana Shahirah; Nor Azman, Nurul Dizyana (2020)
This paper examines the ability of morphological transformation function (MTF) techniques in enhancing the lung nodules in chest x-ray images. Three images of chest x-ray with lung cancer nodules were selected using convenience sampling and retrieved retrospectively in a softcopy format from the free medical online databases. The MTF techniques were performed using the MATLAB software. The images were labelled as Set A (reference image) and Set B (test Image). The Peak Signal-to-Noise Ratio (PSNR) was computed for image quality assessment. In addition, the images were subjectively assessed using the Visual Grading Analysis (VGA). The results show that mean value of PSNR is higher for Set B (21.81) as compared to Set A (21.76). In addition, from the VGA analysis it is found that Set B allows enhancement of image quality and allows correct identification of lung nodules location. In conclusion, the MTF technique potentially give better image quality and delineation of lung nodules in chest x-ray images.